The Federal Council according to the 2005 Constitution between Theory and Practice - Sundus Imran Mohammed Saeed Al-Turahi (Zanco Journal of Human Sciences, 2025)
The two Council systems was and still under discuss the advantages, disadvantages, multiple forms and most important definitions that illustrate the concept, it appears in Britain before 1254, the concept consists of supervision and clergy. And in 1945 Henry III called two nights from every country to participate in parliament and considered as a constitutional precedent of Edward in 1295, after that the model parliament formed which included representatives of the nation’s classes. The decisions were issued by the majority of them and the two councils still on one pace and equal in jurisdiction till 1911 then happened a crisis between lord’s council and Lloyd George about the budget, then the government made parliament law. Because the federal system was old in its origin in constitutional regulation, it’s difficult to clarify what system is without return to or stop in conditions that lead to its origin and development, Britain is the first sight of this system development and spread all over the world. Democracy is the peoples rule for itself to achieve the goals and interests of direct democracy.